Highly Detailed Landfill Mapping and Zoning Based on Multi-sensor Data and Its Analysis - A. Medvedev; A. Medvedev; G. Tepanosyan; G. Ayvazyan; S. Asmaryan (The International Archives of the Photogrammetry, Remote Sensing and Spatial Information Sciences)
The problem of household waste is becoming increasingly relevant in the context of the growing anthropogenic impact on the environment. Many countries are faced with the need to establish an effective system of waste collection, storage, and utilization. However, for decades, this system has not been properly organized in various states, leading to the formation of spontaneous dumps and landfills that are poorly controlled. The Republic of Armenia was not an exception: 174 dumps and landfills of domestic waste were identified on its territory. Of these, only 9 are official municipal landfills, where waste records are kept, and control and reclamation activities are carried out. When the whole sphere of waste management remains in the «grey zone», remote sensing becomes the only effective tool for monitoring the condition of dumps and landfills. Various remote sensing techniques and data types are used to monitor and analyze landfills and landfill sites. Both satellite and unmanned aerial vehicles (UAV) technologies and ultra-high resolution data provide long-term observation and more detailed studies of sites. At the level of individual dumps and landfills, not only waste volumes and other spatial indicators are analyzed, but also a component-by-component study of the waste itself is performed. In addition, the processes occurring on the landfill body are monitored, and the areas surrounding the landfill are studied. This is particularly important as the main environmental impact occurs in this buffer zone. In our study, we examined an urban landfill that has been in operation for over 40 years and found out how the processes taking place there affect the surrounding landscape. Optical, multispectral, and thermal imagery from UAVs were used for detailed analysis and mapping. A series of satellite imagery was also applied to create a long-time series. The optical imagery data served as the basis for creating an orthophoto of the terrain and a digital elevation model, which became the basis for morphometric analysis. Using morphometric indices, thematic maps of exogenous processes occurring in the landfill body and surrounding area were created. Erosion, accumulation processes, and zones of material movement were identified. Multispectral imagery helped to assess the vegetation cover condition and to identify affected areas. Thermal imagery contributed to assessing atmospheric pollution by identifying direct combustion sites, places of landfill gas emission, and the decomposition of domestic waste. Ground geochemical studies, spectroscopy, bioindication, and thermal imaging confirmed the remote sensing results. Based on the data obtained, maps of the territory zoning were created according to various criteria: functional, geochemical, hazards, impact on vegetation cover, and atmospheric pollution. These studies allowed for a comprehensive assessment of the environmental condition of the landfill and the surrounding area, combining remote sensing data with the results of their careful processing.